IMPLEMENTASI ALGORITMA A-STAR PADA PERMAINAN KOMPUTER ROGUELIKE BERBASIS UNITY - Hendi Hermawan; Hari Setiyani (Jurnal Algoritma, Logika dan Komputasi, 2019)
There are many genres found in video games, one of which is role-playing games (RPGs). Roguelike was originally a type of RPG subgenre whose game was based on a risk-aware pattern. The Roguelike game is synonymous with games that require players to play efficiently in order to minimize the risk of losing game progress. This research is in the form of making a Roguelike game by implementing the A-star algorithm to search for the shortest path in the process of chasing enemies against player characters. Overall, this final assignment research is carried out by applying a prototype system development model. The results of this study are able to prove that using the A-star algorithm is one of the right methods for the shortest search in the process of chasing enemies against player characters.Keywords: A-star, Roguelike, unity